Effect of microwave curing on the construction properties of natural soil based geopolymer foam. (10th January 2020) - Nadeem, Muhammad; Ul Haq, Ehsan; Ahmed, Furqan; Asif Rafiq, Muhammad; Hameed Awan, Gul; Zain-ul-Abdein, Muhammad
Highlights: Abundantly available natural soil can be efficiently used for sustainable developments. Positive effect of microwave irradiations on the construction properties of natural soil based Geopolymer foam. Quick and superior properties are achieved in natural soil based Geopolymer foams. Better physical and mechanical properties compared to conventionally ceramic foams were achieved. Abstract: Geopolymer foams are advanced materials having potential to be used as thermal insulators in construction applications to control the environment of building's interior such as temperature. Geopolymer based thermal insulations have attracted more attention due to their sustainability and green to the environment. In this research work, the successful production of geopolymer foam is reported by microwave irradiations using cheaper and eminently available natural soil as aluminosilicate raw material. Slurries with changing quantities of natural soil and sodium silicate were prepared, and foaming was done by microwave irradiations. The minimum thermal conductivity 0.2387 W·m −1 ·K −1 was observed with total porosity 76.89%, bulk density 0.44 g·cm −3, and compressive strength 3.10 MPa for geopolymer foam having 50% natural soil. While maximum compressive strength 8.83 MPa and minimum total porosity 37.82% was achieved at 75% natural soil. Better physical and mechanical Properties of Geopolymer foams were obtained due to using innovative technique which is justified through XRF, FTIR, thermal conductivity, compression test, TGA and DSC analysis. The microstructure analysis is elaborated by SEM.